The Evaluation to the Extent of the Satisfaction of the Bachelor Students of the University of Jordan about the Services that are Presented to them - Albahrat, Fesail; Khawaldah, Bashar (Dirasat: Human and Social Sciences, 2021)
This study comes to evaluate the extension of satisfaction of the University of Jordan students (bachelor students) about the services that are presented to them. It also aims to show the quality of these services inside the campus. The researcher depends on the analytical statistic approach through the tool of questionnaire that was distributed by the method of available sample which is 420 students. The study has reached that there is a high satisfaction among the students of the university of Jordan about the services that are presented to them. It also reached that there is a training for the employees at the University of Jordan library which cause a a stumbling block to the students when they seek any library services. The study calls for improvement of the library technical services inside the the university library and developing it continuously.